Aortic Atherosclerosis and Risk Factors: A Clinico- Demographic Autopsy-Based Study - Mainak Tarafder; Suparna Datta; Ranjan Biswas; Prabir Chakraborty; Saptarshi Chatterjee (Institute of Medico-legal Publications Pvt Ltd, 2022)
Backdrop: Aortic atherosclerosis continues to be a complex process, with the genetic factors, personallifestyles, alterations in local hemodynamics, vascular injury, age related changes, endothelialinflammation and autoimmune diseases, all contributing to its pathogenesis. The scenario ofatherosclerosis in India is appalling with highest loss in potentially productive years of life. As studyof atherosclerosis in living population is difficult, invasive and expensive especially in the developingcountries, autopsy studies have been proved to be a good method for assessing atherosclerosis. So, thepresent study was planned to evaluate the prevalence of atherosclerosis, with the clinic-demographicprofiles of the victims of aortic atherosclerosis and analysing the risk factors associated with it.Material and Methods: This is a cross-sectional descriptive study which was conducted to detectaortic atherosclerosis among all the deceased who got referred to R.G. Kar Medical College PoliceMortuary for autopsy between 1st April to 30th September, 2014.Resusts: Majority of the victims belonged to 4th to 8th decades, with male preponderance in all the agegroups. Though the residence has got no significant implication on atherosclerosis, age turned out tobe the single most culprit in the pathogenesis of atherosclerosis, with hypertwnsion, hyperlipidemia,hyperglycemia and smoking playing their significant parts.Conclusion: The authors feel, in most cases, atherosclerosis can be prevented as most risk factorsassociated with this illness are directly connected with the lifestyle of an individual. In this regard,educational campaign that focuses on informing the members of the society about the dangers ofatherosclerosis, its causes, and the ways of its prevention is likely to reduce the occurrence of thisdisease and thus improve the overall health level of the nation.